Graphene setting the stage: tracking DNA hybridization with nanoscale resolution - Adão, Ricardo M R (2019)
In this study we use nanophotonic effects of graphene to study DNA hybridization: the z−4 nanoscale distance-dependence of the fluorescence lifetime for fluorophores located in the vicinity of graphene is for the first time used to track a DNA hybridization reaction with nanoscale resolution in real time. First, a nanostaircase with ≈2 nm steps from 0 to a total height of 48 nm is used as a nanoruler to confirm the distance dependence law. We find that the axial sensitivity is suited to determine the nanoscale surface roughness of these samples. The proof-of-concept DNA experiments in aqueous medium involve the hybridization of fluorescently labelled DNA beacons attached to CVD grown graphene with complementary (target) DNA added in solution. We track the conformational changes of the beacons statistically by determining the fluorescence lifetimes of the labelling dye and converting them into nanoscale distances from the graphene. In this way, we are able to monitor the vertical displacement of the label during DNA-beacon unfolding with an axial resolution reaching down to 1 nm. The measured distance increase during the DNA hybridization reaction of about 10 nm matches the length of the target DNA strand. Furthermore, the width of the fluorescence lifetime distributions could be used to estimate the molecular tilt angle of the hybridized ds-DNA configuration. The achieved nanoscale sensitivity opens innovation opportunities in material engineering, genetics, biochemistry and medicine.